Responsive shape-shifting nanoarchitectonics and its application in tumor diagnosis and therapy - Shao, Yaru; Xiang, Li; Zhang, Wenhui; Chen, Yuping (Journal of controlled release, 2022)
Nanodrug delivery system has a great application in the treatment of solid tumors by virtue of EPR effect, though its success in clinics is still limited by its poor extravasation, small intratumoral accumulation, and weak tumor penetration. The shape of nanoparticles (NPs) greatly affects their circulation time, flow behavior, intratumoral amassing, cell internalization as well as tumor tissue penetration. Generally, short nanorods and 100–200 nm spherical nanocarriers possess nice circulation behaviors, nanorods and nanofibers with a large aspect ratio (AR) cumulate well at tumor sites, and tiny nanospheres/disks (< 50 nm) and short nanorods with a low AR achieve a favorable tumor tissue penetration. The AR and surface evenness of NPs also tune their cell contact, cell ingestion, and drug accumulation at tumor sites. Therefore, adopting stimulus-responsive shape-switching (namely, shape-shifting nanoarchitectonics) can not only ensure a good circulation and extravasation for NPs, but also and more importantly, promote their amassing, retention, and penetration in tumor tissues to maximize therapeutic efficacy. Here we review the recently developed shape-switching nanoarchitectonics of antitumoral NPs based on stimulus-responsiveness, demonstrate how successful they are in tumor shrinking and elimination, and provide new ideas for the optimization of anticancer nanotherapeutics. [Display omitted]